2013
DOI: 10.12816/0006173
|View full text |Cite
|
Sign up to set email alerts
|

On Some Hadamard Type Inequalities for MT- Convex Functions

Abstract: In this paper, we establish some new Hadamard type inequalities for MTconvex functions and give few applications for some special means.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…In [30] (see also [27,29]), Tunc and Yidirim defined the following so-called MT-convex function: Definition 1.3. A function: I ⊆ R → R is said to belong to the class of MT(I), if it is nonnegative and for all x, y ∈ I and t ∈ (0, 1) satisfies the following inequality: For other recent results concerning Hermite-Hadamard type inequalities through various classes of convex functions, see [1,3,5,7,8,9,12,10,17,20,22,24,25,28] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…In [30] (see also [27,29]), Tunc and Yidirim defined the following so-called MT-convex function: Definition 1.3. A function: I ⊆ R → R is said to belong to the class of MT(I), if it is nonnegative and for all x, y ∈ I and t ∈ (0, 1) satisfies the following inequality: For other recent results concerning Hermite-Hadamard type inequalities through various classes of convex functions, see [1,3,5,7,8,9,12,10,17,20,22,24,25,28] and the references cited therein.…”
Section: Introductionmentioning
confidence: 99%
“…In [29] (see also [26][27][28]), Tunç and Yidirim defined the so-called MT-convex function as follows. A nonnegative function φ : I → R is said to be MT-convex on the interval I if the inequality…”
Section: It Is Also Important To Note Thatmentioning
confidence: 99%
“…In the above propositions we have used the fact that every positive convex function is a MT-convex function [28].…”
Section: Applications To Special Meansmentioning
confidence: 99%
“…In [29] (see also [28]), Tunç and Yidirim defined the notion of MT-convex as follows. Definition 1.6.…”
Section: Definition 15 ([15]mentioning
confidence: 99%
“…For some interesting and significant integral inequalities concerning with the MT-convex functions, one can see in the recent papers [14,21,[27][28][29]. It can be easily observed that convexity means just Jensen-convex when t = In [18],Özdemir et al established inequalities for twice differentiable m-convex functions which are connected with Hermite-Hadamard inequality, and they used the following lemma to prove their results.…”
Section: Definition 15 ([15]mentioning
confidence: 99%